Ablation plus Transarterial Embolic Therapy for Hepatocellular Carcinoma Larger than 3 cm: Science, Evidence, and Future Directions - Lewis, Andrew R.; Padula, Carlos A.; McKinney, J Mark; Toskich, Beau B. (Seminars in Interventional Radiology, 2019)
Thermal ablation is widely regarded as definitive therapy for early-stage hepatocellular carcinoma, but its efficacy decreases in tumors greater than 3 cm. Extensive clinical studies have supported improved outcomes provided through combining transarterial embolic therapy with ablation in the treatment of larger tumors. This article will provide a survey of the science and data for combination therapy in both thermal and nonthermal ablation modalities, as well as describe emerging applications.
Keywords: hepatocellular carcinoma; radiofrequency ablation; microwave ablation; transarterial chemoembolization; transarterial embolization; cryoablation; thermal ablation; combination therapy; ablation; embolization